2007
DOI: 10.1902/jop.2007.060207
|View full text |Cite
|
Sign up to set email alerts
|

Calculus Removal With Diamond‐Coated Ultrasonic Inserts In Vitro

Abstract: In vitro calculus removal was faster with DIs, followed by HIs and PIs. More residual calculus was found with the DIs; however, the 1% to 3% difference (93.7% clean versus 94.6% clean versus 96.9% clean with DIs, PIs, and HIs, respectively) does not seem to be clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(52 reference statements)
0
7
1
Order By: Relevance
“…0%, Max.14.4%). This result was slightly better than findings by Yukna and co-workers, who noted 5.4% remaining calculus using the same instrument [24]. In the latter evaluation, however, an instrumentation time of 90 seconds was even necessary to clean a comparable surface in a similar laboratory setting.…”
Section: Discussioncontrasting
confidence: 48%
“…0%, Max.14.4%). This result was slightly better than findings by Yukna and co-workers, who noted 5.4% remaining calculus using the same instrument [24]. In the latter evaluation, however, an instrumentation time of 90 seconds was even necessary to clean a comparable surface in a similar laboratory setting.…”
Section: Discussioncontrasting
confidence: 48%
“…However, this is only a small improvement and the clinical relevance remains unknown. [ 15 19 ] The aim of such a treatment is to disrupt the subgingival biofilm and in doing so to reduce the pathogens that are present to allow periodontal health to return. [ 20 21 ] Therefore, it isn’t necessary to achieve a plaque reduction of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Through the use of these Teflon coated tips it is possible to manage plaque removal effectively, whereas the removal of hard deposits like calculus seems insufficient. [ 28 ] Diamond-coated scaler tips seem to remove calculus faster,[ 19 ] but lead to more damage of the root surface. [ 29 30 ] Due to the fact that this aspect was not considered in this current study we will do further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the analysis of SEM micrographs showed thatt hese valleys formed by the ultrasonic instrumentation gave the surface a rougher aspect, with several grooves and gouges on root surface. Another explanation for the abrasive capacity of the ultrasonic scaler is the occurrence of burns and hamp on root surface (16), and the fast oscillatory movements of the tip that wear out more root substance leading to the formation of longer and deeper defects and a rougher surface (16). The Gracey curettes and other manual instruments remove several layers of root substance and are intimately dependent on the applied force, angle and sharpness of the curette tip (5).…”
Section: Discussionmentioning
confidence: 99%